Effect of poling temperature on piezoelectric properties of 0-3 PZT-Portland cement composites - Jaitanong N. (2014)
In this work, the effects of poling temperature on the piezoelectric properties such as piezoelectric coefficient (d33) and electromechanical coupling factor (Kt) of 0-3 connectivity PZT-Portland cement (PC) composites were investigated. PZT-PC composites were produced using PZT of 50% by volume and the poling temperatures were selected at 100C, 130C and 160C. The results showed that when using the poling temperature at 130C, the d33 and Kt values were found to be highest at 13 pC/N and 19.39%, respectively.